Development and Validation of e-Modules Integrated with PBL and Local Wisdom to Enhance Critical Thinking and Problem-Solving Skills - Syarful Annam; Agus Ramdani; Muh. Makhrus; Yusuf Sarkingobir (Institute of Multidisciplinary Research and Community Service, 2024)
Abstract: This study develops and validates e-modules incorporating Problem-Based Learning (PBL) and local wisdom to enhance students' critical thinking and problem-solving skills. As 21st-century education emphasizes the integration of technology and innovative strategies, these e-modules aim to support higher-order thinking while preserving cultural values amidst globalization. The research specifically focuses on the topic of Temperature and Heat for Grade VII junior high school science education. Using a Research and Development (RD) approach based on the 4D model Define, Design, Develop, and Disseminate this study completes the development stage, including validation and preliminary testing. In the Define stage, a needs analysis identified that traditional teacher-centered methods inadequately develop students' critical thinking skills. The Design stage systematically structured the e-modules with reflective activities, interactive problem-solving exercises, and integration of local wisdom, leveraging Flip PDF Professional for engaging content creation. The e-modules underwent validation by three expert validators, who evaluated content, presentation, and language. Results showed a validity score exceeding 80% across all criteria, classified as